Data selves more-than-human perspectives - Lupton, Deborah 1963- (Polity Press, 2020)
"As people use self-tracking devices and other digital technologies, they generate increasing quantities of personal information online. Lupton develops a fresh and intriguing perspective on how people make sense of and use their personal data, and what they know about others who use this information"--
Keywords: Datenschutz; Internet; Digitale Daten; Privatsphäre; Information society; Personal information management / Social aspects; Self-monitoring; Electronic surveillance / Social aspects; Digital media / Social aspects; Online social networks; Data protection; Feminist theory; Materialism; Databescherming; Digitale systemen; Informatiemaatschappij; Sociale aspecten